A COST-ANALYSIS OF CATALOGUING AT THE UNIVERSITI SAINS MALAYSIA LIBRARY FOR 1975 - Lee, Chee Hong (1976)
There have been studies on the cost of cataloguing in the developed countries, but these have been done more than a decade ago (1, 2). In recent times, reports tend to be comparative studies of the manual cost of cataloguing to the cost of automated cataloguing for the purpose of the library automation (3, 4). In the case of Malaysia, no cost-analysis of cataloguing has been reported in the literature. It is therefore in this context that this study will primarily provide a guide to cataloguing cost in university libraries, with special reference to the Universiti Sains Malaysia Library. Secondly, in view of the fact that computerised cataloguing may be a distant possibility, this cost-analysis will provide a basis of comparison of the cost of manual and automated systems.